Acute exercise dynamically modulates the hepatic mitochondrial proteome. (5th August 2022) - McCoin, Colin S.; Franczak, Edziu; Washburn, Michael P.; Sardiu, Mihaela E.; Thyfault, John P.
Abstract : Mitochondrial proteomics analysis reveals acute exercise rapidly elicits hepatic proteome remodeling, including pathways related to metabolism, oxidative stress, inflammation, and post-translational modifications. Abstract : Exercise powerfully increases energy metabolism and substrate flux in tissues, a process reliant on dramatic changes in mitochondrial energetics. Liver mitochondria play a multi-factorial role during exercise to fuel hepatic glucose output. We previously showed acute exercise activates hepatic mitophagy, a pathway to recycle low-functioning/damaged mitochondria, however little is known how individual bouts of exercise alters the hepatic mitochondrial proteome. Here we leveraged proteomics to examine changes in isolated hepatic mitochondria both immediately after and 2 hours post an acute, 1 hour bout of treadmill exercise in female mice. Further, we utilized leupeptin, a lysosomal inhibitor, to capture and measure exercise-induced changes in mitochondrial proteins that would have been unmeasured due to their targeting for lysosomal degradation. Proteomic analysis of enriched hepatic mitochondria identified 3241 total proteins. Functional enrichment analysis revealed robust enrichment for proteins critical to the mitochondria including metabolic pathways, tricarboxylic acid cycle, and electron transport system. Compared to the sedentary condition, exercise elevated processes regulating lipid localization, Il-5 signaling, and protein phosphorylation in isolated mitochondria. t-SNE analysis identified 4 unique expressional clusters driven by time-dependent changes in protein expression. Isolation of proteins significantly altered with exercise from each cluster revealed influences of leupeptin and exercise both independently and cooperatively modulating mitochondrial protein expressional profiles. Overall, we provide evidence that acute exercise rapidly modulates changes in the proteins/pathways of isolated hepatic mitochondria that include fatty acid metabolism/storage, post-translational protein modification, inflammation, and oxidative stress. In conclusion, the hepatic mitochondrial proteome undergoes extensive remodeling with a bout of exercise.